(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
Today, ischemic type cerebral circulation disorder (ICC) is one of the most common pathologies in the world. According to the World Health Organization (WHO), BMQAITB is diagnosed in 10-15% of the world’s population, and it ranks second in terms of mortality after acute myocardial infarction. Carotid artery stenosis (Takayasu’s disease) and pathological deformations can be cited as the cause of BMQAITB.